FURTHER OBSERVATIONS ON THE SUITABILITY OF THE MARINE FISH FARM AT MANDAPAM FOR THE CULTURE OF MILKFISH AND GREY MULLETS - Gandhi, V; Raju, A; Rengaswamy, V S; Mohanraj, G; Dorairaj, K (Indian Journal of Fisheries, 2011)
The paper gives an account on the culture of milkflsh Chanos chanos and the grey mullet Valamugilseheli under mono and polyculture systems in the saltwater ponds at Mandapam during the period 1982-1983. Ponds of 2,400 mS (two ponds), 450 m2 (2 ponds) and 200m2 (3 ponds) were used for conductingthe culture experiments. The stocks were fed with a supplementary feed. The growth of fish was betterin polyculture experiments. The rate of production of Chanos chanos was 354-443 kg/ha with a survivalof 73.2-79.9% in monoculture and 422-872 kg/ha with 56.7-70.0% survival in polyculture experiments.V. seheli indicated a production of 200-290 kg/ha and 67-89 kg/ha with the survival rates of 22-91 % and13.3-20.7% in mono and polyculture experiments respectively.